The impact of weather conditions in different years on the biochemical composition of linseed oil - G. A. Popova; N. B. Rogalskaya; N. V. Knyazeva; V. M. Trofimova; T. V. Shelenga; E. A. Porokhovinova; N. B. Brutch (Труды по прикладной ботанике, генетике и селекции)
Background. Linseed oil is a versatile product with varying biochemical composition. Linseed breeding is aimed at producing cultivars with different chemical properties in their oil. The crop is widespread but the environment has a great effect on its fatty acid  biosynthesis.Materials and methods. The impact of weather conditions on the variations in fatty acids composition was studied. Twenty linseed cultivars and accessions of diverse origin and with varying oil composition from the VIR collection were grown in Tomsk Province in 2016–2018. The content of 15 fatty acids (lauric, myristic, palmitic, palmitoleic, margaric, stearic, oleic, cis-vaccenic, linoleic, linolenic, arachidic, eicosenic, arachido nic, behenic, and lignoceric) was assessed in linseed oil using gas–liquid chromatography.Results. The tested material presented a wide diversity of genes controlling different steps of fatty acids biosynthesis and genetic mechanisms involved in the responses to the changing environment. The analysis of variance proved that the content of oleic, linoleic, linolenic and lignoceric acids was controlled solely by the genotype. The content of palmitic and stearic acids was influenced by both the genotype and environment. The synthesis of lauric and cis-vaccenic acids was significantly affected by the weather. Practically all acids, except linoleic and linolenic ones, showed a very high random variation, which in our experiment included genotype × environment interaction. The accessions differed in the range of variation in their characters under diffe rent conditions. There was no definite regularity in the hanges of fatty acid content in the tested genotypes during 3 years.Conclusion. The assessed genotypes probably possess different regulatory mechanisms for fatty acid biosynthesis. Thus, they present a diverse stock for further investigations into fatty acid biosynthesis and for the development of new linseed cultivars widely adaptable to environmental conditions.